2018
DOI: 10.1007/s00424-018-2178-0
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan prevents diet-induced obesity and preserves leptin transport across the blood-brain barrier in high-fat diet-fed mice

Abstract: Obesity is a global health problem and treatment options are still insufficient. When chronically treated with the angiotensin II receptor blocker telmisartan (TEL), rodents do not develop diet-induced obesity (DIO). However, the underlying mechanism for this is still unclear. Here we investigated whether TEL prevents leptin resistance by enhancing leptin uptake across the blood-brain barrier (BBB). To address this question, we fed C57BL/6 mice a high-fat diet (HFD) and treated them daily with TEL by oral gava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 67 publications
5
32
1
Order By: Relevance
“…Once a day, mice received TEL (8 mg/kg bw ) or vehicle by oral gavage in a volume of 5 µL/g body weight. TEL dosages were evaluated recently (Muller-Fielitz et al 2012) and have been confirmed in numerous studies both in rats (Miesel et al 2012, Muller-Fielitz et al 2014, Schuchard et al 2015, Winkler et al 2016, Gustaityte et al 2018 and in mice (Schuster et al 2018, Dapper et al 2019 to reveal antiobese effects. For administration, TEL was suspended in 10% gum arabic (Carl Roth GmbH, Karlsruhe, Germany), resulting in a suspension of 1.6 mg/mL TEL.…”
Section: Study Protocol (Part 1)mentioning
confidence: 95%
See 2 more Smart Citations
“…Once a day, mice received TEL (8 mg/kg bw ) or vehicle by oral gavage in a volume of 5 µL/g body weight. TEL dosages were evaluated recently (Muller-Fielitz et al 2012) and have been confirmed in numerous studies both in rats (Miesel et al 2012, Muller-Fielitz et al 2014, Schuchard et al 2015, Winkler et al 2016, Gustaityte et al 2018 and in mice (Schuster et al 2018, Dapper et al 2019 to reveal antiobese effects. For administration, TEL was suspended in 10% gum arabic (Carl Roth GmbH, Karlsruhe, Germany), resulting in a suspension of 1.6 mg/mL TEL.…”
Section: Study Protocol (Part 1)mentioning
confidence: 95%
“…Weight loss was observed both when telmisartan (TEL) was administered daily via the oral route to rats with fully diet-induced obesity in a treatment setting (Muller-Fielitz et al 2014) and in patients during irbesartan therapy (Kintscher et al 2007). These antiobese effects were only observed after giving high dosages of the drug and were found to be class effects and independent both of blood pressure reduction and of peroxisome proliferator-activated receptor gamma (PPARγ) activation (Muller-Fielitz et al 2011, Schuster et al 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hippocampal injury is found in HFD-fed animals in response to increased blood-brain barrier permeability [71] due to circulating proinflammatory adipokines and reactive glial cytokine production [81]. Increased blood-brain barrier permeability that allows proinflammatory proteins into the hippocampus can initiate neuroinflammation and stimulate neurodegeneration [82].…”
Section: Mechanisms Responsible For High-fat Diet-induced Cognitivmentioning
confidence: 99%
“…All data presented herein were obtained from refs. [44,54,55,70,72,74,75,78,88,95,96,98,102–111,116,119–121,124–130,132,134–137,140–144,147–156,158,159,161,163–171,173–176...…”
Section: Diet Composition and Exposure Timementioning
confidence: 99%